Reconstruction of vitamin C test worksheet for junior high school with ANCOR stages - Novita Resti; Bambang Supriatno; Amprasto Amprasto (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Practicum is one of the learning methods that can help students construct various psychomotor, higher-order thinking skills and characterize learning outcomes. One factor determining the practicum's success is the use of worksheets. However, currently, many worksheets do not meet the standards and do not show knowledge construction. In addition, there has been no research on the reconstruction of the vitamin C test worksheet. Therefore, it is necessary to analyze and reconstruct the vitamin C test worksheet. The method used is descriptive qualitative with three stages: analysis, trial, and reconstruction. The population in this study was represented by vitamin C test worksheets for junior high school class VIII used by teachers. The sample in this study was one of the worksheets used in learning at school, circulating on the internet, and having incomplete components. The sampling technique was purposive sampling. The analysis showed that the worksheet does not comply with the standards, so it is necessary to reconstruct the worksheet so as not to cause errors in student practicum activities. The reconstruction of this worksheet can be an alternative to overcome the current worksheet's shortcomings.Abstrak. Praktikum merupakan salah satu metode pembelajaran yang dapat membantu siswa mengonstruksi berbagai keterampilan psikomotorik, berpikir tingkat tinggi, dan mengkarakterisasi hasil belajar. Salah satu faktor penentu keberhasilan praktikum adalah penggunakan lembar kerja siswa. Namun, saat ini, masih banyak lembar kerja siswa yang tidak memenuhi standar dan tidak menunjukkan konstruksi pengetahuan. Selain itu, belum ada penelitian mengenai rekonstruksi lembar kerja uji vitamin c. Oleh karena itu, perlu dilakukan analisis dan rekonstruksi lembar kerja uji vitamin c. Metode yang digunakan adalah deskriptif kualitatif dengan tiga tahapan yaitu analisis, uji coba dan rekonstruksi. Populasi dalam penelitian ini adalah lembar kerja siswa mengenai uji vitamin c di Sekolah Menengah Pertama kelas VIII yang digunakan oleh guru. Sampel dalam penelitian ini adalah salah satu lembar kerja yang digunakan dalam pembelajaran di sekolah, beredar di internet dan komponennya tidak lengkap. Teknik pengambilan sampel adalah purposive sampling. Hasil analisis diperoleh bahwa lembar kerja siswa belum memenuhi standar sehingga perlu dilakukan rekonstruksi agar tidak menimbulkan kesalahan dalam kegiatan praktikum siswa. Rekonstruksi lembar kerja ini dapat menjadi lembar kerja alternatif  untuk mengatasi kekurangan lembar kerja yang ada saat ini.